Personal factors influencing the decision to choose eco-friendly airlines at Chiang Mai International Airport - Maneerat, Phichaya; Thanaboonruang, Suthamanee (วารสารวิชาการการบิน การเดินทาง และการบริการ, 2025)
As the environmental impact of the airline industry becomes a growing concern for both travelers and policymakers, demand for sustainable aviation continues to intensify. Despite the recent global growth in eco-friendly air travel options, research on Thai consumers’ attitudes and behaviors toward green airlines, and eco-friendly flight options in Thailand, remains limited. To address this gap, this study investigates how “personal factors” would influence Thai consumers’ decisions to choose environmentally friendly airline services. As an extension, this study provides research-based recommendations to support airlines design targeted marketing strategies for eco-friendly passengers, which are in accordance with the International Civil Aviation Organization’s (ICAO) sustainability goals. For the purposes of this study, quantitative research was conducted on 420 passengers at Chiang Mai International Airport. Furthermore, this study employed a ‘one-way ANOVA’ method for the purposes of its statistical analysis. The results revealed that age, education, and income significantly influenced passengers’ decisions to fly with eco-friendly airlines, while gender appeared to have had little to no impact regarding this selection. These findings highlight the importance of targeting well-educated, middle-aged, and higher-income travelers who are more likely to choose sustainable options. However, the scope of this study is limited to a single airport. Future research may conduct at various airports across Thailand and apply mixed-method research to gain deeper information about Thai consumer behavior related to sustainable aviation.